A close-up view of the wood cell wall ultrastructure and its mechanics at different cutting angles by atomic force microscopy - Casdorff, Kirstin; Keplinger, Tobias; Rüggeberg, Markus; Burgert, Ingo (Planta, 2018)
The structural assembly of wood constituents within the secondary cell wall has been subject of numerous studies over the last decades, which has resulted in contradicting models on the spatial arrangement and orientation of the wood macromolecules. Here, we use multichannel atomic force microscopy by means of quantitative imaging, to gain new insights into the macromolecular assembly. Cross-sections of spruce wood, which had been cut at different angles ranging from 0° to 30° were investigated. Strikingly, depending on the cutting angle, the structural appearance of the S₂ layer changed from a network-like structure to a distinct concentric lamellar texture. This makes us conclude that the often visualized lamellar organization of the secondary cell wall is not the consequence of a continuous inherent ring pattern, but rather a result of the specific surface cross-section appearance of cellulose aggregates at larger cutting angles. By analyzing the recorded force distance curves in every pixel, a nano-mechanical characterization of the secondary cell wall was conducted. Substantially lower indentation modulus values were obtained compared to nanoindentation values reported in the literature. This is potentially due to a smaller interaction volume of the probe with a by far less deep indentation.